Adolf Deissmann: Ein (zu Unrecht) fast vergessener Theologe und Philologe - Breytenbach, Cilliers; Markschies, Christoph (Novum Testamentum, Supplements, 2019)
The chapters in this volume cover all aspects of the work of Adolf Deissmann (1866-1937). Following his main works, the authors highlight crucial aspects and impulses from his philological work on the New Testament, including the interpretation of Paul, Light from the Ancient East, the social status of the first Christians, and the lexicography of the New Testament. His background in the Lutheran Church of Hessen-Nassau, his contribution to the ecumenical movement together with Nathan Söderblom and through the Evangelische Wochenbriefe during World War II, and his role as rector of the Berlin University in 1930/1931 are also discussed. The contributions illustrate that notwithstanding his ecumenical engagement, Deissmann never gave up his scholarly work. The essays trace the influence of his philological and historical work among his students and place contemporary debates on Deissmann as philologist and theologian in their historical context. Dieser Band widmet sich in neun Einzelbeiträgen der gesamten Breite des Schaffens von Adolf Deissmann (1866-1937). Entlang der Hauptwerken werden wesentliche Aspekte und Impulse aus seiner philologisch orientierten Arbeit am Neuen Testament neu gewürdigt (Interpretation der Paulusbriefe, Licht vom Osten , "Unterschichtenthese", neutestamentliche Lexikographie et cetera). Daneben geht es um seine Herkunft aus der Evangelischen Kirche in Hessen-Nassau, um sein Wirken in der Ökumene am Beispiel der Beziehung zu Nathan Söderblom und der Arbeit an den Evangelischen Wochenbriefen im Ersten Weltkrieg sowie um seine Rolle als Rektor der Berliner Universität von 1930 bis 1931. Die Beiträge zeigen, dass Deissmann trotz seines ökumenischen Engagements seine wissenschaftliche Arbeit nicht aufgegeben hat. Die Aufsätze gehen den Wirkungen seiner philologisch-historischen Arbeit unter seinen Schülern nach und stellen die zeitgenössischen Debatten um den Philologen und Theologen Deissmann in ihren historischen Kontext.